Interactions of homocysteine and conventional predisposing factors on hypertension in Chinese adults. Issue 11 (24th September 2017) - Yang, Boyi; Fan, Shujun; Zhi, Xueyuan; He, Jing; Ma, Ping; Yu, Luyang; Zheng, Quanmei; Sun, Guifan
Abstract : This study aimed to investigate whether conventional predisposing factors modify the associations of homocysteine with blood pressure levels and hypertension. A total of 2615 adults were recruited from Liaoning province. An elevated homocysteine level was significantly associated with increased hypertension risk and blood pressure (all P <.05). Interaction analyses showed that homocysteine acted synergistically with age, overweight/obesity, dyslipidemia, and family history of hypertension to affect hypertension risk, and the relative excess risk due to interaction was 1.21 (95% confidence interval, 0.07–2.35), 0.72 (95% confidence interval, 0.07–1.36), 0.45 (95% confidence interval, 0.06–0.85), and 1.87 (95% confidence interval, 0.77–2.97), respectively. Increases in blood pressure were higher in patients who were overweight/obese or had a family history of hypertension than in their counterparts (all P interaction <.05). This study provides some strong evidence for interactions of homocysteine with conventional predisposing factors on hypertension.